Water-Soluble Polyaniline/Polystyrene Sulfonate Synthesized Using Dialysis Membrane. Issue 2 (22nd January 2017) - Kang, Kyung Seok; Jee, Chan Hyuk; Kim, Taeyoon; Chung, Ildoo; Huh, PilHo
ABSTRACT: Relatively narrow molecular weight distribution polyaniline/poly(4-styrene sulfonate) were synthesized by aqueous chemical oxidation polymerization using a dialysis membrane as the key to controlling the diffusion speed of the initiator. The optical, electrochemical, and electrical properties of the resulting polyaniline/poly(4-styrene sulfonate) were estimated by ultraviolet–visible–near infrared spectroscopy, cyclic voltammetry, and four-point probe. Compared to a bulk polyaniline/poly(4-styrene sulfonate), the resulting polyaniline/poly(4-styrene sulfonate) showed relatively high crystallinity according to X-ray diffraction, and their polydispersity indices ranged from 1.6 to 2.0 as a function of the reaction time. The electrical conductivities of the resulting polyaniline/poly(4-styrene sulfonates) were also enhanced gradually with increasing reaction time. GRAPHICAL ABSTRACT: